Management of Pastures and Rangeland in Arid Western Rajasthan: A Review - Yadava, N D; Soni, M L; Rathore, V S; Bagdi, G L; V, Subulakhsmi; Gaur, Mahesh K (Annals of Arid Zone, 2019)
Ranges and pastures are the backbone of the arid zone animal rearing. The climatic adversities, fodder availability, large animal population in the region completely depends on these pastures. Heavy grazing pressure, poor management and poor rainfall conditions are only responsible for poor yield and low carrying capacity (0.68 ACU ha-1) of these ranges and grasslands. The restoration by reseeding and introduction of perennial grasses, shrubs and bushes are the only option for increasing the productivity. Response to 20 kg N ha-1 application to grasses appeared to be favorable in arid regions having less than 300 mm rainfall. Growing trees such as Prosopis cineraria, Acacia nilotica and Zizyphus nummularia, and grasses Cenchrus ciliaris, C. setigerus, Dactyloctenium scindicum, Panicum antidotale, and Lasiurus scindicus together has also been a traditional practice in the Thar Desert. The agri-horti-silvicultural system having fruit trees + fodder crops + fast growing nitrogen fixers tree species providing good fodder for animals is another option for increasing the intensity of crops and increase productivity per unit area. Additionally, grazing management like rotational grazing is most important for maintaining the sustainable production. Key words: Range management, pastures, grass cover, grazing management